Archeologia nowożytna nadwiślańskiego Fordonu (Kronika Bydgoska, 2010)
Many interesting archaeological objects, dating back to the modem times (15th-19th c.c.), come from the area of Fordon District. The most important items include graves discovered in 2007 next to St Nicholas’ Church. Interesting are also relics of 17,h-19th-century streets, preserved under the present-day road surface. Significant are also individual archaeological artefacts from Fordon, e.g. fragments of clay tobacco pipes, glassware and earthenware. Ali these historical artefacts show different aspects of the everyday life of Fordon residents in the modem times.